ANALISIS EFEKTIVITAS PENGGUNAAN PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) UNTUK PENINGKATAN PERTANIAN BERKELANJUTAN - Callista Fabiola Candraningtyas; Muhammad Indrawan (Pusat Studi Pembangunan Pertanian dan Pedesaan (PSP3), 2023)
The increase in the world's human population is a significant challenge for agricultural and food production. This causes farmers to use excessive chemical fertilizers so that they exploit fertile land to meet human food needs. This challenge has also caused Indonesia to be ranked third highest in Southeast Asia with a global hunger index. So that conditions do not get worse, it is necessary to carry out sustainable agricultural practices that are environmentally friendly. This sustainable agricultural practice can be carried out using Plant Growth Promoting Rhizobacteria (PGPR). The method used in this study was to make inoculants and PGPR liquid formulations which were then applied to Red Beans to observe their development and compared to Red Beans which were not given PGPR liquid. The study found that the impact of using PGPR on Red Beans was that it could increase plant height, leaf height, and number of leaves. This proves that the use of PGPR can be an effective solution to be applied to agriculture in Indonesia.